Anthropogenic noise impairs foraging for cryptic prey via cross-sensory interference - Halfwerk, Wouter (Proc Biol Sci, 2020)
Anthropogenic noise levels are globally rising with profound impacts on ecosystems and the species that live in them. Masking or distraction by noise can interfere with relevant sounds and thereby impact ecological interactions between individuals of the same or different species. Predator–prey dynamics are particularly likely to be influenced by rising noise levels, with important population- and community-level consequences, as species may differentially adapt to noise disturbance. Acoustic noise can, however, also impair the use of visual information by animals through the process of cross-sensory interference, possibly impacting species interactions that have so far been largely ignored by noise impact studies. Here, we assessed how noise affected the performance of great tit (Parus major) foraging on cryptic prey. Birds trained individually to search for paper moths differing in the level of camouflage with the test background were tested in the presence and absence of noise. We found that noise significantly increased approach and attack latencies, but that the effect depended on the level of crypsis. Noise increased latencies for cryptic prey targets, but not for conspicuous and colour-matched prey targets. Our results show that noise can interfere with the processing of visual information, particularly in difficult tasks such as separating objects from a similar looking background. These results have important ecological and evolutionary implications as they demonstrate how globally rising anthropogenic noise levels can influence the arms race between predators and prey across sensory domains.